Problematika Penggunaan Gadget pada Anak Usia Dini di Masa Pandemi Covid-19 Lingkungan V Kelurahan Tanjung Rejo Kecamatan Medan Sunggal - Dinni Mawarni; Hadis Purba; Enny Nazrah Pulungan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
The aim of this research is to find out the problems of using gadgets in early childhood, the factors that cause problems in using gadgets in early childhood, parents' efforts to overcome the problems of using gadgets in early childhood during the COVID-19 pandemic, Environment V, Tanjung Rejo Village, Medan Sunggal District . This research was conducted using a descriptive qualitative approach. The subjects in this research were parents of children aged 1-6 years in Environment V, Tanjung Rejo Village, Medan Sunggal District. The researcher's data collection process used interview, observation and documentation methods. Analysis of the data obtained by the author uses the Miles and Hubermen concept, namely data analysis, data reduction, data presentation, and drawing conclusions. The results of this research reveal: 1) the problem of using gadgets in early childhood during the COVID-19 pandemic is that children are addicted to watching YouTube, children's emotions are uncontrolled and children are less responsive when called; 2) the factor causing problems in using gadgets in early childhood during the COVID-19 pandemic is the busyness of parents to make their work easier and seeing the family environment playing with gadgets; 3) parents' efforts to overcome the problem of using gadgets in early childhood during the COVID-19 pandemic include providing alternative games, giving gadgets when the battery is low, hiding gadgets from children, being strict about prohibiting children, not filling internet quotas.